Household water insecurity is strongly associated with food insecurity: Evidence from 27 sites in low‐ and middle‐income countries. Issue 1 (24th August 2019) - Brewis, Alexandra; Workman, Cassandra; Wutich, Amber; Jepson, Wendy; Young, Sera; ,
Abstract: Objectives: Food and water insecurity have both been demonstrated as acute and chronic stressors and undermine human health and development. A basic untested proposition is that they chronically coexist, and that household water insecurity is a fundamental driver of household food insecurity. Methods: We provide a preliminary assessment of their association using cross‐sectional data from 27 sites with highly diverse forms of water insecurity in 21 low‐ and middle‐income countries across Africa, Asia, the Middle East, and the Americas (N = 6691 households). Household food insecurity and its subdomains (food quantity, food quality, and anxiety around food) were estimated using the Household Food Insecurity Access Scale; water insecurity and subdomains (quantity, quality, and opportunity costs) were estimated based on similar self‐reported data. Results: In multilevel generalized linear mixed‐effect modeling (GLMM), composite water insecurity scores were associated with higher scores for all subdomains of food insecurity. Rural households were better buffered against water insecurity effects on food quantity and urban ones for food quality. Similarly, higher scores for all subdomains of water insecurity were associated with greater household food insecurity. Conclusions: Considering the diversity of sites included in the modeling, the patterning supports a basic theory: household water insecurity chronically coexists with household food insecurity. Water insecurity is a more plausible driver of food insecurity than the converse. These findings directly challenge development practices in which household food security interventions are often enacted discretely from water security ones.